U-SR ISOTOPIC SPEEDOMETER: FLUID FLOW AND CHEMICAL WEATHERING RATES IN AQUIFERS - Maher K.; DePaolo D.J.; Christensen J.N. (My University, 2006)
Both chemical weathering rates and fluid flow are difficult to measure in natural systems. However, these parameters are critical for understanding the hydrochemical evolution of aquifers, predicting the fate and transport of contaminants, and for water resources/water quality considerations. 87Sr/86Sr and (234U/238U) activity ratios are sensitive indicators of water-rock interaction, and thus provide a means of quantifying both flow and reactivity. The 87Sr/86Sr values in ground waters are controlled by the ratio of the dissolution rate to the flow rate. Similarly, the (234U/238U) ratio of natural ground waters is a balance between the flow rate and the dissolution of solids, and ?-recoil loss of 234U from the solids. By coupling these two isotope systems it is possible to constrain both the long-term (ca. 100’s to 1000’s of years) flow rate and bulk dissolution rate along the flow path. Previous estimates of the ratio of the dissolution rate to the infiltration flux from Sr isotopes (87Sr/86Sr) are combined with a model for (234U/238U) to constrain the infiltration flux and dissolution rate for a 70-m deep vadose zone core from Hanford, Washington. The coupled model for both (234U/238U) ratios and the 87Sr/86Sr data suggests an infiltration flux of 5 ? 2 mm/yr, and bulk silicate dissolution rates between 10-15.7 and 10-16.5 mol/m2/s. The process of ?-recoil enrichment, while primarily responsible for the observed variation in (234U/238U) of natural systems, is difficult to quantify. However, the rate of this process in natural systems affects the interpretation of most U-series data. Models for quantifying the ?-recoil loss fraction based on geometric predictions, surface area constraints, and chemical methods are also presented. The agreement between the chemical and theoretical methods, such as direct measurement of (234U/238U) of the small grain size fraction and geometric calculations for that size fraction, is quite good.
Keywords: AQUIFER; CHEMICAL WEATHERING; DISSOLUTION; FLUID FLOW; STRONTIUM ISOTOPE; URANIUM ISOTOPE; WATER-ROCK INTERACTION